Legal Protection for Consumers at the Medan Oil Palm Research Center (PPKS) - Hasyim; Reza Setiawan; Daud Dwi Pandu; Cinthia Tasyva Zetira; Sapira Dini Azahra (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research entitled Legal Protection for Consumers at the Medan Oil Palm Research Center (PPKS) Company, aims to find out how the legal protection given to consumers of Oil Palm Sprouts at the Medan Oil Palm Research Center is in accordance with applicable laws. This research was conducted in Medan and the target respondents were people who had purchased sprout products at the Medan Oil Palm Research Center (PPKS). The type of research used in this study uses a descriptive method with a qualitative approach. The data collection technique in this study was to use questionnaires and literature studies. The data analysis technique used to find information and answers in research is to sort out important data and then describe it in the form of an explanation accompanied by documentary evidence and by distributing questionnaires to be filled out by research respondents.